E-Commerce Perjalanan Wisata pada Agent Piknik Again Berbasis Website - Joseph Fredrik; Jullend Gatc (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Picnic Again is a travel agent that offers travel services. This travel agent has been running for a long time and has a very attractive travel package. The registration system is still through on social media, which when registering becomes effective. As for when registering there was a surge, namely the number of customers who registered. In this study, research used a prototype to design this website, which can overcome the problems in this travel agent. Data sources obtained by research through observation and interviews make it easier for research to create this website. Through the implementation and evaluation of the system through blackbox testing, it can be concluded that the website designed by the research was succsessful and ran without error. This website designed by research alleviates the problem and facilities service of Piknik Again become more efficient and effective.